(untitled) (UNED Research Journal, 2021)
Introduction: The persistence of coat color polymorphisms, such as the coexistence of the melanistic coat color (black) and "wild type" (spotted), is an evolutionary enigma. Objective: The predictions of Gloger’s Rule and the Temporal Segregation hypothesis were tested, which propose that melanistic individuals (a) will occur more frequently in dense tropical forest than in open habitat due to the advantages of camouflage and thermoregulation, and (b) will be most active during the brightest times of the circadian and lunar cycle because black pigmentation is cryptic under bright light. Methods: Based on 10 years of jaguar and oncilla camera trap records from dense tropical forest in Costa Rica, the activity patterns and relative abundance of non-melanistic (rosetted or spotted) versus melanistic morphs was compared. Results: Twenty-five percent of jaguar records in dense forests were melanistic compared to the global average of 10% in open and closed habitats; 32% of oncilla records were melanistic compared to 18% overall in Brazil. Overlap analysis indicated that melanistic jaguars were more active during daylight hours compared to non-melanistic jaguars, which were more nocturnal and crepuscular. Likewise, melanistic oncilla were more diurnal than non-melanistic oncilla; melanistic oncilla were also more active during the full moon, while the non-melanistic oncilla were less active. Conclusion: These results imply that melanistic jaguar and oncilla enjoy the adaptive benefits of superior camouflage when inhabiting dense forest and accumulate a fitness advantage when hunting in brighter light conditions. If true, natural selection would ensure that melanistic individuals persist when dense forest is retained but may be threatened by deforestation and accelerating human presence.